Use of metallic stents in the management of stenotic bowel stomas - Mohammad Arabi; Hasan Aljaziri; Mohammed Rashid Akhtar; Tim Fotheringham (Society of Gastrointestinal Intervention, 2022)
Bowel stoma stenosis resulting in bowel obstruction can be managed conservatively by dietary changes, or by surgical revision of the stenotic/retracted stoma. Metallic stent placement is a minimally invasive procedure that can help alleviate symptoms and obviate the need for surgical interventions, especially in non-surgical candidates or patients with progressive malignant obstruction. This report demonstrates the use of image-guided metallic stent placement in patients with stenotic stomas due to different underlying pathologies.